المناسبة بين أسماء السور وموضوعاتها: دراسة تطبيقية على السبع الطوال = The relevance between the names of the Surahs and their subjects: an applied study on the Seven Long Surahs - Alshahrani, Mohammed Saeed Ayed; Khaled, Nashwan Abdo (Al-Azhar University, Egypt, 2024)
The names of the surahs constitute clear connotations and indications of the Qur’anic meanings, and its linguistic and moral secrets. This study aims to reveal some aspects of the correspondence between the name of the Qur’anic surah and its subject, by studying the names of the surahs (The Seven Tall) and explaining the aspects of naming and their reasons, the general purposes of the surah, and the correspondence between the name of The surah and its content, in order to find out the eloquence of the name, and the forms of connection of these names with the central topics and purposes in it. This research is not an analytical collection, but rather an invitation to use reason, contemplation, and deduction, to reveal multiple aspects of the Qur’anic structure. To illuminate insights, and reveal flowing meanings, by linking the names of the surahs with their contents, which is a promising research horizon in the sea of Qur’anic studies.